Pengembangan Media Prototype sebagai Media Pelatihan dengan Topik Pewarnaan Dip Dye pada Kostum Karakter Odette Swan Lake di Arva School of Fashion - Stefani Cinthia Karellina; Lutfiyah Hidayati; Deny Arifiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The media has a very important role in a learning and teaching activity. Media is divided into several types, including visual media, audio media, audio visual media, and all kinds of media. The media at Arva School of Fashion is often created and developed for use in workshops is prototype media. Prototypes media for materials or coloring topics using the dip dye technique at the Arva School of Fashion are not yet available. Related to this, a prototype media was made from material coloring using the dip dye technique which was applied to making character costumes. The purpose of making this prototype media is of course so that teaching and learning activities can easily achieve something you want, because the media is a good intermediary in communication. This media prototype development research uses the 4D model development method with descriptive data processing methods. The development method with the 4D model approach consists of Define, Design, Development, and Disseminate. The results of this study state the flow of the prototype development process and the results of the prototype.